Application of Environmentally Friendly Concepts in Sustainable Technology: A Conceptual Study as a Guide for Researchers - Ximenes Guterres, Juvinal; Suprapto, Eko (Greenation International Journal of Engineering Science, 2024)
This study raises environmental and sustainability issues. This research consists of several parts. First, the literature review focuses on orientation towards the application of environmentally friendly concepts in the use of sustainable technology. Second, the research model and propositions developed in this study are based on a literature review of previous studies, such as the relationship between environmentally friendly orientation towards green innovation and green competitive advantage, as well as the relationship between green innovation. Furthermore, the application of environmentally friendly concepts is explored and linked to the use of sustainable technology. Where in the context of an environmentally friendly orientation strategy, companies have an important role in being aware and encouraged to produce environmentally friendly products to build sustainable competitive advantages in the long term. Thus, this study also shows that environmentally friendly product innovation and environmentally friendly competitive advantages are important strategies for reducing environmentally friendly organizational behavior.